Special Education: policies and teaching-learning processes - Marcia Denise Pletsch; Geovana Mendonça Mendes Lunardi (Arizona State University, 2014)
Since the 1990`s, the social and educational rights of people with handicap and other atypical developmental conditions have received significant attention in the Brazilian public policies and financial investments. In this perspective, this dossier presents results of research developed in different states of the country, in which we can identify the impacts of these rights in policy guidelines, curriculum and schooling processes historically destined for these subjects, as well as research methodologies and resources required to secure those rights. They also indicate problems and tensions that involve teacher formation in face of the demands placed by the school inclusion policy. In this respect, the studies presented here reveled the multiplicity of factors that involve the elaboration and implementation of inclusive policies in a country with great social inequalities, but, above all, show the importance and the need of this type of proposal in order to guarantee the acknowledgement of the diversity present in Brazilian society and schools.